Doktrin Corporate Negligence Pertanggunggugatan Entitas Hukum Rumah Sakit di Indonesia - Lumunon, Theodorus Hendrik Willem; Maramis, Ronny A (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 3 (2023), 2023)
Article 46 of Law No. 44 of 2009 on Hospitals regulates corporate counterclaims involving hospitals as legal entities under the vicarious liability doctrine. However, these regulations do not fully align with hospitals' distinct characteristics. Hospitals have a unique structure with three functional units: the supervisory board, the board of directors, and various professional groups, each with distinct responsibilities. This writing examines issues surrounding Article 46, including whether hospitals should be held accountable for damages caused by healthcare human resources. It explores when hospital corporations should face litigation and when healthcare human resources should assume liability based on professional responsibility. Despite the clarity of Article 46's text, its application doesn't entirely consider hospitals' organizational uniqueness. The objective is to establish regulations and legal principles to address challenges in applying Article 46, contributing to an ideal concept of corporate counterclaims involving hospitals. The research adopts a normative juridical approach, including legislative analysis, conceptual exploration, case study, and comparative law. The research suggests a concept of hospital liability as a legal entity, contingent on four conditions: the hospital has an obligation based on the corporate negligence doctrine, breach of these obligations occurs, quantifiable losses result, and a demonstrable causal connection exists between the breach and resulting damages.